2017
DOI: 10.2298/vsp151023159c
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status in children with inherited dystrophic epidermolysis bullosa

Abstract: Background/Aim. Epidermolysis bullosa is a group of rare, genetic connective tissue diseases that cause blisters in the skin and mucosal membranes. The aim of this study was to evaluate the oral health status of patients with epidermolysis bullosa dystrophica and level of knowledge and opinion of parents about the implementation of preventive measaures and quality of dental care of affected children. Methods. This study included a group of 17 patients from Serbia suffering from dystrophic epidermolysis bullosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The clinical burden of microstomia (abnormally small oral orifice) was reported in three studies [21,48,50]. [50]; the average maximal mouth opening in this patient cohort was 24.3 mm (SD, 11.6 mm).…”
Section: Microstomiamentioning
confidence: 66%
See 4 more Smart Citations
“…The clinical burden of microstomia (abnormally small oral orifice) was reported in three studies [21,48,50]. [50]; the average maximal mouth opening in this patient cohort was 24.3 mm (SD, 11.6 mm).…”
Section: Microstomiamentioning
confidence: 66%
“…In three studies of neonates with RDEB, the vast majority of infants developed blisters within one week of birth (range of 70% to 94%; Table 1 ) [ 16 , 33 , 35 ]. Five studies reported on the incidence of oral blisters or lesions in patients with RDEB [ 21 , 22 , 33 , 43 , 48 ]. The proportion of patients experiencing these lesions ranged from 79 to 100% [ 33 , 43 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations